2016
DOI: 10.1007/s10237-016-0853-7
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear stress exposure time: a Lagrangian measure of near-wall stagnation and concentration in cardiovascular flows

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms suitable in regions of complex hemodynamics that are traditionally difficult to quantify, yet encountered in many disease scenarios. Keywords: advection-diffusion; blood flow; hemodynamics; near-wall transport; residence time; shear stress; p. 2 IntroductionBiomechanical interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 59 publications
3
51
0
1
Order By: Relevance
“…As expected, an increase in plaque growth expands this backflow region. Such regions may have important implications for near‐wall accumulation of atherogenic biochemicals and cells . Moreover, changes in WSS fixed points and manifolds may be visualized downstream of the stenosis as the plaque grows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, an increase in plaque growth expands this backflow region. Such regions may have important implications for near‐wall accumulation of atherogenic biochemicals and cells . Moreover, changes in WSS fixed points and manifolds may be visualized downstream of the stenosis as the plaque grows.…”
Section: Resultsmentioning
confidence: 99%
“…First, low WSS is known to induce inflammatory endothelial cell (EC) behavior, which promotes the atherogenic processes in plaque development. Second, low WSS has been shown to be correlated with near‐wall biochemical accumulation and stagnation, which may promote atherosclerosis. Based on similar observations, Zohdi developed a very simple ODE model to simulate WSS‐driven plaque growth .…”
Section: Introductionmentioning
confidence: 99%
“…The similarity in qualitative surface concentration patterns for different diffusion coefficients suggests that near‐wall convection patterns dominate surface concentration distribution in high–Péclet‐number mass transport problems. Recently, Arzani et al computed Lagrangian coherent structures (LCS) in the wall shear stress (WSS) vector field to study near‐wall convective transport and demonstrated how the attracting WSS LCS correspond to high surface concentration patterns. Although WSS LCS have been suggested for high‐Schmidt‐number ( scriptOfalse(103false) and higher) mass transport, we have shown that high surface concentration localization patterns are robust with respect to changes in mass diffusivity and therefore the Schmidt number.…”
Section: Discussionmentioning
confidence: 99%
“…However, reliable mechanical properties and vessel thickness measurements of all arterial blood vessels are necessary before attempting more rigorous 3D fluid‐structure interaction simulations for large sections of the cerebral vasculature. In addition, near‐wall hemodynamic risk analysis can be extended to more WSS components such as Lagrangian processing of the WSS vector field …”
Section: Discussionmentioning
confidence: 99%
“…In addition, near-wall hemodynamic risk analysis can be extended to more WSS components such as Lagrangian processing of the WSS vector field. 3,72 Another future improvement concerns the use of non-Newtonian blood flow rheology. 73 This step would be critical for blood vessels less than 100 μm in diameter.…”
Section: Limitation and Future Workmentioning
confidence: 99%